Coordination tailoring of water-labile 3D MOFs to fabricate ultrathin 2D MOF nanosheets. Issue 24 (16th June 2020) - Wen, Yuehong; Liu, Qiang; Su, Shaodong; Yang, Yuying; Li, Xiaofang; Zhu, Qi-Long; Wu, Xintao
Abstract : A coordination tailoring top-down delamination strategy involving the controllable partial disassembly of a water-labile 3D MOF has been explored to fabricate ultrathin 2D MOF nanosheets. Abstract : A novel coordination tailoring top-down delamination strategy involving the controllable partial disassembly of water-labile 3D MOFs has been explored to fabricate ultrathin 2D MOF nanosheets, and it exhibits many advantages such as green, convenience and high efficiency. Accordingly, 2D ultrathin MOF nanosheets with a two-fold interpenetrated architecture have been rapidly obtained from a 3D pillar-layered MOF, and they show distinguished fluorescence responses to different solvents.